Impacts of ocean-atmosphere interaction phenomena on hydrometeorology of the Gurupi river watershed, Eastern Amazon - Gomes, Dênis José Cardoso; Beltrão, Norma Ely Santos (Revista Brasileira de Climatologia, 2024)
Extreme events impact in hydrometeorology of Amazonian watersheds. The objective of this research was to analyze the effects of climate extremes on rainfall and discharge variability in a watershed in Eastern Amazonia. Climatic indices, hydrometeorological and spatial data were acquired for the analysis of the watershed of the Gurupi river. Calculations of correlation, efficiency, detection of a difference in distribution, and trend of changes in hydroclimatic variability were applied, in addition to using the Rainfall Anomaly Index. There is a greater influence of the tropical Atlantic on precipitation, as well as precipitation on the Gurupi upper flow. Significant differences were detected in rainfall distribution, as well as increasing and decreasing trends. Regional climatology is marked by the highest (smaller) rainfall in the North (South), with extremes and anomalous years. The Gurupi basin is impacted by climate extremes. Evidence suggests vulnerability to the region's climate and the need for preventive measures.